Landscape of heart proteome changes in a diet-induced obesity model - Vileigas, Danielle F. [UNESP]; Harman, Victoria M.; Freire, Paula P. [UNESP]; Marciano, Cecília L. C. [UNESP]; Sant’Ana, Paula G. [UNESP]; de Souza, Sérgio L. B. [UNESP]; Mota, Gustavo A. F. [UNESP]; da Silva, Vitor L. [UNESP]; Campos, Dijon H. S. [UNESP]; Padovani, Carlos R. [UNESP]; Okoshi, Katashi [UNESP]; Beynon, Robert J.; et al. (Springer Nature, 2019)
Obesity is a pandemic associated with a high incidence of cardiovascular disease; however, the mechanisms are not fully elucidated. Proteomics may provide a more in-depth understanding of the pathophysiological mechanisms and contribute to the identification of potential therapeutic targets. Thus, our study evaluated myocardial protein expression in healthy and obese rats, employing two proteomic approaches. Male Wistar rats were established in two groups (n = 13/group): control diet and Western diet fed for 41 weeks. Obesity was determined by the adipose index, and cardiac function was evaluated in vivo by echocardiogram and in vitro by isolated papillary muscle analysis. Proteomics was based on two-dimensional gel electrophoresis (2-DE) along with mass spectrometry identification, and shotgun proteomics with label-free quantification. The Western diet was efficient in triggering obesity and impaired contractile function in vitro; however, no cardiac dysfunction was observed in vivo. The combination of two proteomic approaches was able to increase the cardiac proteomic map and to identify 82 differentially expressed proteins involved in different biological processes, mainly metabolism. Furthermore, the data also indicated a cardiac alteration in fatty acids transport, antioxidant defence, cytoskeleton, and proteasome complex, which have not previously been associated with obesity. Thus, we define a robust alteration in the myocardial proteome of diet-induced obese rats, even before functional impairment could be detected in vivo by echocardiogram.